Plan de gestión de residuos provenientes de la faena de mariscos y residuos comunes del Puerto Artesanal Pesquero de Esmeraldas (PAPES) - Guzmán Cevallos, Luis Alfredo (2014)
This project was made to propose a waste management system to Esmeraldas Fish Port, it started analyzing the current port situation, this study took economical, technological and logistical factors and some bibliographic sources which help to determine the physical, biotic and socioeconomic components in the area. Then, the technical visits allowed to identify the main generating source, also the amount and composition waste, it was found that 2261,23 Kg slaughtering fish waste (53,07%), 1708,86 Kg food waste (40,10%) and plastic, paper, glass and other (6,83%). Finally, based on the work done, there was establish some segregation mechanisms, store, transportation and waste disposal that allowed an appropriate management waste system. Furthermore some recyclable waste can be sold in order to produces an economic income to the port.